The Effectiveness of CEFR Model-based Material on Arabic Essay Writing (Kitabah Hurrah) Ability - bin Abdul Hakim, Muhammad Kamal; Setiadi, Syamsi; Tajuddin, Shafruddin; Miftahuddin, Ahmad (KnE Social Sciences, 2024)
The study aimed to determine how well CEFR-based writing instruction affects students’ ability to write essays in Arabic. A single-group experimental design was used in this study. The research sample included approximately 50 students participating in essay writing courses. A random sample was carried out for obtaining data using tests, documents, and observations. Paired sample t-test was used to analyze the data. The study results suggest that the CEFR-based model material can improve Arabic essay writing relatively easily. Since t-Stat < t-table (-25.189 < 2.0095), H0 is refuted according to the t-test, and H1 is accepted. It indicates that teaching materials are suitable for classroom use and positively impact students’ Arabic writing skills. The post-test results showed that based on the data distribution, the highest score was 90, and the lowest was 60. Most students now receive grades between 85 and 88. The results of this study provide educators and academic institutions with a better understanding of how to create relevant, student-centered teaching materials that impact students’ language skills. Keywords: Arabic, CEFR, essay, writing